Outstanding participation of Unillanos with the presentation of 25 research projects, in external calls of the Ministry of Science, Technology and Innovation (Contexto (Universidad de los Llanos), 2024)
During the first four months of 2024, the General Directorate of Research of the Universidad de los Llanos has supported and encouraged the participation of Unillanos teachers in five calls made by the Ministry of Science, Technology and Innovation (MinCiencias) and the General Royalties System (SGR), managing to submit 25 projects.The Technical Director of Research, Yohana María Velasco Santamaría, highlighted the commitment and dedication of the teachers of the three faculties of Unillanos, Faculty of Basic Sciences and Engineering (FCBeI), Faculty of Agricultural Sciences and Natural Resources (FCAyRN) and Faculty of Human Sciences and Education (FCHyE), in participating in calls 34, 35, 36, 948 and 950, of MinCiencias and the General Royalties System.
Keywords: sustainable development; human capital; training; Innovation